Theory, Practice, and Analysis of Indonesia ’s Foreign Policy - Fadlan Muzakki (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2017)
Indonesian foreign policy is considered as a uniqe and rare policy. This is because the main focus of Indonesian foreign policy is Free and Active. For country like Indonesia which had just got independence in 1945, the country is considered as a country with a pioneer foreign policy to stand in a non-block. Therefore, Indonesia was quite popular with non-block movement and Bandung Conference in the Cold War Period. This paper discusses Indonesian foreign policy and match its policy with underlying theory of Foreign Policies: Realism, Idealism, and Constructivism. Moreover, this essay also analyses Indonesian Foreign Policy through Middle Power Concept. Additionally, this essay also explains the practices of Indonesian Foreign Policy in current years, especially under Joko Widodo ’s Administration. Last but not least, the author also reveals Indonesian foreign policy and its relations to media, society or public opinion.